(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Patients with chronic abdominal pain get repeated hospitalization. They fail to perform their duties continuously and thus become burdens for their families. These patients are occupying a good number of indoor beds with dilemmatous diagnosis. This indirectly creates pressure on health care facility and plays a notable negative role to our economy. Aim: To determine the usefulness of diagnostic laparoscopy for diagnosis and also to find out the therapeutic scope in unexplained abdominal pain. Method: This is a prospective cross-sectional observational study and was carried out in the Department of surgery, CMH, Dhaka over a period of 2 years from July 2008 to June 2010. Results: Among the study population, 8 (26.67%) patients underwent abdominal and pelvic operation in the past for various diseases. The duration of chronic abdomen pain in these patients was between 6 months to 24 months or more. Twenty five (83.5%) cases out of 30 were diagnosed. Postoperative band & adhesions (28%), recurrent appendicitis (24%), endometriosis (16%), abdominal tuberculosis (16%) were the most frequently found etiologies of unexplained chronic abdominal pain in these patients. Eighteen (59.4%) patients underwent therapeutic procedure during Diagnostic Laparoscopy and biopsy was taken from 7 (23.1%) patients. Patients were provided treatment according to histopathology report. Patients were followed up for 2 years at Out Patient Department (OPD) at CMH. Around 75% cases became symptom free following therapy, 15% had short term minimal symptom for 6 months and persistent pain was present in small percent of patients (10%). 09 JAFMC Bangladesh. Vol 10, No 2 (December) 2014 Conclusion: Laparoscopy is a safe diagnostic modality. It is useful to establish diagnosis or for exclusion of suspected abdominal pathology whenever chronic abdominal complaints remain undiagnosed. It also provides an opportunity for definitive treatment by laparoscopy or open surgery in unsuspected lesions. Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014